Gum Arabic as a potential candidate in quorum quenching and treatment of periodontal diseases - Hashim, Nada Tawfig; Babiker, Rasha; Rahman, Mohammed Mustahsen; Chaitanya, Nallan C. S. K.; Mohammed, Riham; Dasnadi, Shahistha Parveen; Gismalla, Bakri Gobara (Frontiers in Oral Health, 2024)
Periodontal diseases are chronic inflammatory conditions influenced by bacterial biofilm formation and host immune responses, affecting millions worldwide. Traditional treatments like mechanical debridement and systemic antibiotics often face limitations, including biofilm resilience and antibiotic resistance. Gum Arabic (GA), a natural exudate from Acacia trees, presents a promising alternative with its anti-biofilm and anti-inflammatory properties. This review highlights the role of GA in periodontal therapy, particularly its ability to interfere with quorum sensing (QS) pathways, specifically the AI-2 signaling system used by key periodontal pathogens such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum. By disrupting QS, GA inhibits biofilm formation, reduces bacterial virulence, and promotes a balanced oral microbiome. GA's prebiotic properties also encourage the growth of beneficial bacteria, enhancing the host's immune response while preserving the systemic microbiome. Clinical studies demonstrate GA's effectiveness as an adjunct in periodontal therapy, with significant reductions in plaque accumulation, gingival inflammation, and bleeding. This highlights GA's potential as a natural therapeutic agent, offering an effective, antibiotic-sparing option in managing periodontal disease. However, further research is warranted to fully establish GA's role in comprehensive periodontal care and its long-term benefits.